HOW TO TRANSLATE AN ACTION VERB PROVIDE INTO BAHASA INDONESIA THROUGH THE NATURAL SEMANTIC METALANGUAGE - sudipa, I nengah (Lingual Journal of Language and Culture; Vol 6 No 2 (2018): Lingual: Journal of Language and Culture, 2019)
A bstract This study is aimed at mapping the meaning of action verb provide and its translation in Indonesian lexicons. The data sources of this study are two Colours Magazines of Garuda Indonesia, May 2017 and March 2018 editions. In colleting the data, this study applied the observation method and note taking technique. Those data were analyzed using Natural Semantic Metalanguage (NSM) approach proposed by Anna Wierzbicka (1996). Furthermore, the method of analyzing data was descriptive qualitative method. First, each of the data was analyzed to find its meaning configuration. Then, it was followed by the paraphrasing using semantic primitives to show the explication of each lexicon and be able to compare them. The results of this study shows that the action verb provide is translated into five different Indonesian lexicons in the Colours Magazine. The verb and its translations have slight differences shown by the meaning configurations as well as explications. However, they could properly deliver the intended meaning for the Indonesian target readers regarding the sentences they are in.